PENGARUH ETOS KERJA DAN RELIGIUSITAS TERHADAP KINERJA KARYAWAN BMT AL BAROKAH NGLUWAR SALAM MAGELANG (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
This study aims to analyze employee performance in terms of work ethic and religiosity. This research is a quantitative research. This research method uses a questionnaire given to 70 employees of BMT Al Barokah Ngluwar Salam Magelang as a sample with purposive sampling technique. Measurement of variables using a Likert Scale. Data analysis using multiple regression analysis. The results of the analysis show that work ethic and religiosity affect employee performance.
Keywords: Religiosity; Employee Performance